Measuring and Improving Walkability in Urban Historical Tourism Area: A Case Study in Medan - Eddy, Firman; Abdillah, Wahyu; Novrial; Affif, Aulia Malik (International Journal of Architecture and Urbanism, 2026)
Medan is the largest city on Sumatera Island and the capital city of North Sumatera. The main tourist attractions are in the downtown area, which is located in the Kesawan corridor, around Lapangan Merdeka, Maimun Palace, and the Al Mashun Grand Mosque. However, there is still no adequate walking environment that connects those areas which resulting in very little walking activity. This research aims to to assess the current condition of the walking environment and develop a design model in order to enhance walkability in the historic tourism areas of Medan. The authors undertake a field survey as well as collect the pedestrians preference regarding the walkway. The final walkability score of the research locations are 58,8. The authors proposed five model recommendation to improve the walkway in the research locations, namely: (1) Walkway amenities improvement; (2) CPTED design application in the walkway; (3) Implementation of pelican crossing; (4) Signage and speed bump application; and (5) Ramp and S portal barrier application. The authors believed the proposed model recommendations are sufficient to enhance the walkability in the research locations.